Discretion of the Minister of Trade in the Sugar Import Case of 2015–2016 and the Limits of Authority and Accountability in State Administrative Law - Hadi Mustopa; Metty Sander; Franciscus Xaverius Wartoyo (International Journal Labs, 2025)
Indonesia, as a state based on the rule of law, adheres to the principle that every governmental act must be grounded in applicable regulations. Nevertheless, in practice, there are circumstances not explicitly addressed by legal provisions, creating the necessity for public officials to exercise discretionary authority. Discretion serves as a mechanism that enables flexibility in administrative decision-making to address legal gaps while remaining within the limits of existing legal frameworks. This study examines the concept, scope, principles, and boundaries of discretionary authority in administrative law and evaluates the Minister of Trade’s exercise of such authority in the 2015–2016 sugar import case. Employing a normative juridical method with legislative and conceptual approaches, this research reveals that discretion is tightly regulated to prevent abuse of power, including the requirement of procedural compliance and inter-agency coordination. The findings from the sugar import case demonstrate that although the Minister’s policy was intended to serve the public interest, it did not comply with procedural coordination requirements and breached established procedures, thereby raising disputes over the legality of the discretionary action. The study concludes that discretion must always be carried out in accordance with the principles of legality, accountability, and effective coordination between relevant governmental bodies. This study contributes to clarifying the boundaries between legitimate discretion and abuse of authority within Indonesia’s state administrative law framework.